Analisis Risiko Penggunaan Program ESPK PT Konimex Sukoharjo Dengan Metode Octave Allegro: Penerapan Manajemen Risiko dalam Kalibrasi Program ESPK: Peningkatan Mutu di Industri Farmasi - Santoso, Yohanes Marcellino; Dwika Cahyono, Ariya (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
This study analyzes the risks associated with the ESPK (Electronic Calibration Request) Program at PT Konimex Sukoharjo using the Octave Allegro method. The ESPK program is utilized for calibration processes, and the research aims to determine whether the program poses potential risks to the company. The Octave Allegro method is used to evaluate threats and information security risks, enabling the organization to make decisions based on risks to the confidentiality, integrity, and availability of critical information assets. Data obtained indicate a Relative Risk Score of 28, meaning the risks can be mitigated or postponed. The findings involve users of the ESPK program, such as calibration admins, validation officers, calibration technicians, information system managers, and the owners of calibrated equipment. Key risks identified include data input errors, server downtime or maintenance during working hours, and incomplete program features. All these risks can either be mitigated or postponed. In conclusion, PT Konimex has not previously conducted a risk analysis on the ESPK program, and the Octave Allegro method identifies threats and risks for better protection of information assets.